2022
DOI: 10.14202/vetworld.2022.419-426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E supplementation on chicken sperm quality: A meta-analysis

Abstract: Background and Aim: Among several factors, the sperm quality of poultry is affected by the rooster's body size and the availability of antioxidants like vitamin E. This study aimed to determine the effect of dietary vitamin E supplementation on rooster sperm quality through a meta-analysis. Materials and Methods: After verification and evaluation, a total of 19 articles were included in this study. Data, including dietary vitamin E, semen volume, concentration, total sperm cells, pH, motility, viability, perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The evaluation temperature effect viability 26⁰C and 5⁰C (Figure 2) showed preservation at 26⁰C for 9 hours with the viability of 42.19±1.31% was significant (p<0.05), lower than that of 5 ⁰C with the viability of 54.1±5.78 %. This result is in line with Eslami et al, (2016) and Hayanti et al, (2022) that sperm preserved at 4⁰C may produce life ability better than at 27⁰C. Cold preservation was also reported to protect sperm viability, as metabolism can be depressed with minimum activities (Ervandi et al, 2020;Triadi et al, 2022).…”
Section: Evaluation Of Semensupporting
confidence: 77%
See 2 more Smart Citations
“…The evaluation temperature effect viability 26⁰C and 5⁰C (Figure 2) showed preservation at 26⁰C for 9 hours with the viability of 42.19±1.31% was significant (p<0.05), lower than that of 5 ⁰C with the viability of 54.1±5.78 %. This result is in line with Eslami et al, (2016) and Hayanti et al, (2022) that sperm preserved at 4⁰C may produce life ability better than at 27⁰C. Cold preservation was also reported to protect sperm viability, as metabolism can be depressed with minimum activities (Ervandi et al, 2020;Triadi et al, 2022).…”
Section: Evaluation Of Semensupporting
confidence: 77%
“…Semen evaluation consists of visual evaluation, such as Volume, color (Peters et al, 2008), and microscopic evaluation, such as sperm concentrations, motility (%), normality (%), and viability of sperm (Arifiantini, 2012;Ervandi et al, 2020;Hayanti et al, 2022). Macroscopic evaluation, the Volume of semen was measured by sucking on the 1 ml graded syringe.…”
Section: Semen Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu, Huang, Liang, Zheng, & Wang, 2015;Yue et al, 2010). A meta-analysis also concluded that dietary supplementation level of Vitamin E significantly affected sperm concentration, motility, viability, sperm fertility and the number of sperm cell deaths in chicken (Hayanti et al, 2022). And semen quality and the blood plasma testosterone were improved in the 4 dogs with poor semen quality after the 50 mg Vitamin E treatment (Kawakami, Kobayashi, Hori, & Kaneda, 2016).…”
Section: Roles Of Vitamin E In Spermatogenesismentioning
confidence: 98%
“…According to certain research, oxidative stress plays a crucial role in the onset and evolution of diabetes mellitus as well as the emergence of diabetic complications including diabetic nephropathy 5 . Recent research holds that the pathophysiology of diabetic nephropathy is directly related to inflammation and the activation of the innate immune system 6 .…”
Section: Introductionmentioning
confidence: 99%